A Rare Case of Chorea-Acanthocytosis in India: Clinical Presentation, Diagnosis, and Management - Challa, Anusha; Kumar, Ritesh; Manthena, Sai Preeti; Nallapati, Shreya (Biomedical Sciences and Clinical Medicine, 2025)
Chorea-acanthocytosis (ChAc) is a rare autosomal recessive neurodegenerative disorder classified under Neuroacanthocytosis syndromes. It is characterized by progressive neurological decline, psychiatric symptoms, and the presence of irregularly shaped red blood cells (acanthocytes) on peripheral blood smears. ChAc remains underdiagnosed due to its rarity and variable presentation. This case report describes a 44-year-old male from India, born of a consanguineous marriage, who presented with self-mutilating lip-biting or lingual dystonia, generalized chorea, and a history of seizures. The patient exhibited psychiatric symptoms including depression and agitation in addition to neurological features such as hypophonic speech, slowed saccades, and hypotonia. Initial diagnoses of tardive dyskinesia and generalized tonic-clonic seizures were revised following referral to neurology. Peripheral blood smears revealed acanthocytosis, and whole-exome sequencing confirmed a homozygous mutation in the VPS13A gene, leading to the diagnosis of ChAc. MRI findings included bilateral caudate and lentiform nucleus atrophy, with mild cerebral atrophy. The patient was treated symptoms were managed with antiepileptics, dopamine receptor antagonists, anticholinergics and vitamin supplementation, and vitamin supplementation, resulting in significant improvement in mandibular and lingual symptoms. Dental guards were provided to prevent further oral injury. This case highlights the importance of considering ChAc in patients presenting with neuropsychiatric and movement disorder symptoms, especially in the context of consanguinity. Early recognition and multidisciplinary management are crucial to improving quality of life. By documenting this rare case, we aim to enhance clinical awareness and facilitate early diagnosis of ChAc in resource-limited settings.